Mugabe`s Dilemma: Zimbabwe and land Reform at Independence and Beyond - Nyawo-Viriri-Shava, Vongai Z. (Universal Academic Services, 2016)
After 90 years of white domination, the promise of independence meant freedom at last for Zimbabweans. Many had lost their land in the interim, lost their sons, lost their livelihoods not even to mention the hopelessness embedded in being colonized. Expectations were high as was the pressure to deliver on the young leader Mugabe, in 1980 at independence. This article seeks to trace and explain the trajectory of the land reform processes in Zimbabwe from independence and beyond. The central trial of the paper being to explain the diverse difficulties Mugabe and the new government faced. To explain the mammoth tusk the nascent democracy had, the researcher carried out interviews with people who fought in the liberation struggle second Chimurenga, ordinary citizens as well as farmers in different parts of Zimbabwe